Creatie als opdracht : Kunst in Genk 2004-2006. - Cloostermans, Mark; Descheemaeker, Geertje; Dietvorst, Els; Geuns, Guido; Gonissen, Willo; Guldolf, Eddie; Legierse, Thérèse; Mylle, François; Op de Beeck, Steven; Reulens, Kristof; Rzoska, Björn; Vanmechelen, Koen (Genk : Stad Genk - Dienst Cultuur, 2007)
Baumsteiger, Felix ; Berger, Wout ; De Bodt, Els ; Devillé, Jozef ; Dietvorst, Els ; Van Dingenen, Filip ; Fabro, Luciano ; Gonnissen, Willo ; Hamelryck, Ado ; Van Isacker, Philip ; Jochems, Gert ; Lipkens, René ; Mertens, Marco ; Mertens, Pierre ; Nicolodi, Renato ; Rombouts, Guy ; Tinel, Koenraad ; Vanmechelen, Koen
boek